2019
DOI: 10.1042/bsr20182448
|View full text |Cite|
|
Sign up to set email alerts
|

Ribophorin II promotes cell proliferation, migration, and invasion in esophageal cancer cells in vitro and in vivo

Abstract: Esophageal cancer is a common digestive tract cancer, which is a serious threat to human health. Ribophorin II (RPN2) is a part of an N-oligosaccharyltransferase complex, which is excessively expressed in many kinds of cancers. In the present study, we explore the biological role of RNP2 in esophageal cancer. First, we found that the expression of RPN2 was higher in esophageal cancer tissues than in adjacent non-tumor tissues, and negatively correlated with E-cadherin expression. RPN2 expression levels in esop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Next, targets of miR-378e were explored and here we first confirmed RPN2 as a functional target of miR-378e in glioma. Accruing studies suggested RPN2 as an oncogene in multiple cancers, including breast cancer, colon carcinoma, nasopharyngeal carcinoma and esophageal cancer [30][31][32][33]. Hence, we hypothesized that RPN2 might be also as a carcinogenic gene in glioma.…”
Section: Discussionmentioning
confidence: 95%
“…Next, targets of miR-378e were explored and here we first confirmed RPN2 as a functional target of miR-378e in glioma. Accruing studies suggested RPN2 as an oncogene in multiple cancers, including breast cancer, colon carcinoma, nasopharyngeal carcinoma and esophageal cancer [30][31][32][33]. Hence, we hypothesized that RPN2 might be also as a carcinogenic gene in glioma.…”
Section: Discussionmentioning
confidence: 95%
“…RPN2, TUSC, as well as DDOST are the subunits of OST. The expression of RPN2 is positively correlated with the progression of breast cancers ( Ono et al, 2015 ), non-small cell lung ( Fujita et al, 2015 ), gastric ( Fujimoto et al, 2018 ), esophageal ( Li et al, 2019 ), and colorectal cancers ( Bi and Jiang, 2018 ), whereas TUSC3 was reported as a candidate tumor suppressor ( VaơíčkovĂĄ et al, 2018 ). DDOST, which also acted as advanced glycation end product-receptor 1 ( Li et al, 1996 ), had been reported in regulating AGE, which increased oxidative stress and inflammation and may be involved in liver injury and subsequent carcinogenesis ( Moy et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…27 Besides, Li et al found that esophageal cancer cell proliferation and metastasis could be suppressed by RPN2 knockdown. 28 In HCC, Huang et al confirmed that RPN2 was a vital regulator to promote the malignant progression of HCC. 29 Our study presented that RPN2 was highly expressed in HCC.…”
Section: Discussionmentioning
confidence: 99%